2022
DOI: 10.3390/su14031610
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Increasing Income Inequality and Poverty: Analysis by Income Source

Abstract: The high and persistent level of income inequality limits the opportunities for economic growth and contributes to the persistence of a high poverty rate in Russia. Reducing inequality is integral to achieving the Sustainable Development Goals (SDG-10); thus, greater focus is needed to reduce income inequality. We assess income inequality based on a representative income and expenditure data collected at the micro level to determine the risk of increasing inequality and poverty in the context of specific socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Combined with related research [8], some other factors will also have the ability to influence on the urban-rural areas income gap. To avoid those factors impact on the results, the following 4 variables will be taken as control variables.…”
Section: Control Variablesmentioning
confidence: 99%
“…Combined with related research [8], some other factors will also have the ability to influence on the urban-rural areas income gap. To avoid those factors impact on the results, the following 4 variables will be taken as control variables.…”
Section: Control Variablesmentioning
confidence: 99%
“…Moreover, some studies reported that the enhancement of the product market monopoly will cause the labor share to decrease [38]; however, for factor market distortion, the existing research primarily discussed the effect arising from the labor market control and negotiation ability, capital market regulation, and the reform of state-owned enterprises on the labor share [39,40]. There have been significant but small differences between the capital return and the economic growth rate, thus having powerful and destabilizing effects on the structure and evolution of social inequality in the long run [41].…”
Section: Theoretical Analysis and Mechanism Test Model Settingmentioning
confidence: 99%
“…Poverty alleviation is the most important indicator in the Sustainable Development Goals (SDGs), which emphasize the need for a reduction of inequality and the eradication of global poverty in all forms by 2030 [1,2]. As one of the most dynamic economies in the world, China has not only achieved sustained economic growth, but also achieved world-renowned achievements in poverty eradication.…”
Section: Introductionmentioning
confidence: 99%